GAMBARAN TINGKAT PENGETAHUAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DAN KESEHATAN LINGKUNGAN PADA ANAK USIA SEKOLAH DASAR - Shisi Gusnita; Arneliwati Arneliwati; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
School-age children were susceptible age group to health problems and they were more susceptible to disease. The low student knowledge level about clean and healthy behaviors and environmental health that would be triggers the emergences of several kinds’ diseases. This research aimed at describing the knowledge level of clean and healthy behaviors and environmental health for student at state elementary School 147 Pekanbaru. This research used descriptive quantitative design with cross sectional approach. This research used 175 respondents using stratified non random sampling technique. Univariate analysis was used in this research. The findings of this research showed that the characteristics of respondents’ majorities were 91women (52%) and the knowledge level of clean and healthy behaviors were in good category that amounts118 respondents (67.42%). The knowledge was in very good category, but the knowledge level of environmental health in the school was in enough categories which amounts 87 respondents (49,7%). Therefore, it could be concluded that the students' knowledge level about environmental health were still low, so it needed to be improved to avoid disease Keywords: Clean and Healthy Behaviors; Environmental Health; Knowledge; School-Age Children.